A brief look at the least-squares approach as a classifier applied to restricted-vocabulary speech recognition - Guido, Rodrigo Capobianco [UNESP]; Rodrigues, Luciene Cavalcante (My University, 2012)
In this letter, a speech recognition algorithm based on the least-squares method is presented. Particularly, the intention is to exemplify how such a traditional numerical technique can be applied to solve a signal processing problem that is usually treated by using more elaborated formulations.
Keywords: least-squares method; speech recognition; intelligent transfer functions